IMPLEMENTASI SISTEM ENTERPRISE RESOURCE PLANNING MODUL POINT OF SALE MENGGUNAKAN METODE QUICKSTART - Salsabila Aulia Choirunisa; Nuur Wachid Abdul Majid (LPPM Universitas Abdurrab, 2026)
This research aims to document and evaluate the implementation of an Enterprise Resource Planning (ERP) system based on Odoo, specifically the Point of Sale (POS) module, at Rumah Buket by Rere, a small business operating in the creative retail sector of flower bouquet sales. Prior to system implementation, transaction recording, inventory management, and raw material purchasing were conducted manually, which led to potential recording errors and delays in information availability. This research adopts a case study approach using the QuickStart implementation method, which consists of the Kick-Off Call, Analysis, and Configuration stages, to align the ERP system with the specific business needs of the SME. System evaluation was carried out through Black Box Testing to ensure that system functionalities operated as expected, as well as User Acceptance Test (UAT) designed based on the Technology Acceptance Model (TAM) to assess user acceptance. The testing results indicate that all main system functions operated properly. Furthermore, the UAT results show a high level of user acceptance, with Perceived Ease of Use (PEOU) reaching 88% and Perceived Usefulness (PU) reaching 89%, indicating that the system is considered easy to use and provides tangible benefits in supporting daily operational activities. The implementation of the Odoo POS module successfully integrated sales processes, inventory management, and purchase recording in a more structured and efficient manner compared to the previous manual approach. This study contributes practical documentation of ERP implementation and evaluation using the QuickStart method in the context of creative retail SMEs and may serve as a reference for similar businesses planning to adopt ERP systems to improve operational efficiency and data accuracy.